2016
DOI: 10.1007/s12272-015-0701-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnesium carbonate on the solubility, dissolution and oral bioavailability of fenofibric acid powder as an alkalising solubilizer

Abstract: To investigate the possibility of developing a novel oral pharmaceutical product using fenofibric acid instead of choline fenofibrate, the powder properties, solubility, dissolution and pharmacokinetics in rats of fenofibrate, choline fenofibrate and fenofibric acid were compared. Furthermore, the effect of magnesium carbonate, an alkalising agent on the solubility, dissolution and oral bioavailability of fenofibric acid was assessed, a mixture of fenofibric acid and magnesium carbonate being prepared by simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…12 Therefore, choline fenofibrate can be taken regardless of food, whereas traditional fenofibrate needs to be taken immediately after meals. 13 After 8 weeks of combination therapy, there was a 45.57% reduction in TG levels, and 65.57% of the patients achieved the target TG level of 150 mg/dL. The pharmacologic potency of choline fenofibrate in this study is not inferior to that reported in previous studies.…”
Section: Discussionsupporting
confidence: 40%
“…12 Therefore, choline fenofibrate can be taken regardless of food, whereas traditional fenofibrate needs to be taken immediately after meals. 13 After 8 weeks of combination therapy, there was a 45.57% reduction in TG levels, and 65.57% of the patients achieved the target TG level of 150 mg/dL. The pharmacologic potency of choline fenofibrate in this study is not inferior to that reported in previous studies.…”
Section: Discussionsupporting
confidence: 40%
“…First, to investigate the enhancement of stability of D‐cycloserine via alkalizing agents, the mixtures of D‐cycloserine and each alkalizing agent were stored at the accelerated stress condition of 60 °C/75% RH for 2 days, and the remaining concentrations of D‐cycloserine were determined . Meglumine, precipitated calcium carbonate, magnesium oxide, sodium bicarbonate, calcium silicate, magnesium aluminosilicate, and sodium citrate dehydrate were employed as the alkalizing agents . The remaining concentrations in the D‐cycloserine alone was nearly 0% (Figure ), suggesting that D‐cycloserine were very unstable in this accelerated stress condition.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 illustrates the X-ray diffractions of the samples. The diffractogram indicates that the pure FA is crystalline as demonstrated by specific peaks at the diffraction angles (2θ) of 18°, 19°, 21°, and 23° [9] with crystallinity value 86.69%. According to the XRD pattern, the recrystallized FA had more diverse peak intensities than the pure FA, and only one peak appeared at (2θ) 23° with crystallinity value 79.90%.…”
Section: Powder X-ray Diffraction (P-xrd)mentioning
confidence: 99%